2015
DOI: 10.1039/c4sm02296c
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of the dispersing agent polysorbate 80 on liquid crystalline nanoparticles of soy phosphatidylcholine and glycerol dioleate

Abstract: Well-defined, stable and highly structured I2 (Fd3̅m) liquid crystalline nanoparticles (LCNP) of 50/50 (wt/wt) soy phosphatidylcholine (SPC)/glycerol dioleate (GDO), can be formed by using a low fraction (5-10 wt%) of the dispersing polymeric surfactant polyoxyethylene (20) sorbitan monooleate (polysorbate 80 or P80). In the present study we used small angle neutron scattering (SANS) and deuterated P80 (d-P80) to determine the location and concentration of P80 within the LCNP and small angle X-ray scattering (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…This effect is rather pronounced at high P80 concentrations, where even the loss of internal particle structure can occur. 22,25 In our earlier work 13 with the same DGMO/GMO-50/P80/water system as studied here, we were also able to form nanoparticles with highly swollen sponge phase structures over a wider range than in the pure lipid-aqueous system. Cryo-TEM imaging showed that such phases could be dispersed into sponge-like nanoparticles (L 3 -NPs) that featured a dense sponge phase core with swollen bilayer structures at the interface.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…This effect is rather pronounced at high P80 concentrations, where even the loss of internal particle structure can occur. 22,25 In our earlier work 13 with the same DGMO/GMO-50/P80/water system as studied here, we were also able to form nanoparticles with highly swollen sponge phase structures over a wider range than in the pure lipid-aqueous system. Cryo-TEM imaging showed that such phases could be dispersed into sponge-like nanoparticles (L 3 -NPs) that featured a dense sponge phase core with swollen bilayer structures at the interface.…”
Section: Introductionsupporting
confidence: 53%
“…Soy phosphatidylcholine (SPC)/glycerol dioletate (GDO)/polysorbate 80 (P80) LCNP were found to form lipid multilayers on anionic silica that increase in thickness with P80 concentration. 22,24 However on cationic silica, intact LCNP were found to deposit without being dependent on the P80 concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of Polysorbate-80 (P-80), a surfactant, prevents to some extent the binding of polymyxin to microtiter plate [4]. However, CLSI or EUCAST guidelines never approved the use of P-80 for colistin or polymyxin B ST.…”
mentioning
confidence: 99%
“…In vitro ST of colistin is challenging and is influenced by: i) multicomponent composition of colistin; ii) cationic property of colistin attributes for adherence to the microtiter plate; iii) heteroresistance to colistin [1] Adherence of colistin or polymyxin B to microtiter plates is reported as the major technical issues by many investigators across the world [3]. The addition of Polysorbate-80 (P-80), a surfactant, prevents to some extent the binding of polymyxin to microtiter plate [4]. However, CLSI or EUCAST guidelines never approved the use of P-80 for colistin or polymyxin B ST.…”
mentioning
confidence: 99%